2019
DOI: 10.1186/s12964-019-0434-3
|View full text |Cite
|
Sign up to set email alerts
|

CXCL1-LCN2 paracrine axis promotes progression of prostate cancer via the Src activation and epithelial-mesenchymal transition

Abstract: Background Mechanisms driving the progression of castration-resistant prostate cancer are believed to relate substantially to the tumor microenvironment. However, the cross-talks between tumor epithelial cell, stromal cells, and immune cells are yet to be fully elucidated. The present study aims to determine the role of chemokine and neutrophil derived cytokine paracrine axis in mediating the interaction between tumor cells, stromal myofibroblasts, and neutrophils in the tumor microenvironment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 45 publications
(46 reference statements)
1
46
0
Order By: Relevance
“…Interestingly, various chemokines have been implicated to contribute to EMT progression in cancer cells. EMT can be induced by CXCL8 and its receptors through overexpression of the transcription factor Brachyury [141], CCL2 with the enhancement of Snail expression [142], the CXCL6/CXCR1/2 axis via the PI3K/AKT and Wnt/β-catenin pathways [143], and the CXCL1/LCN2 paracrine axis with the activation of Src signalling [144]. In addition, NF-κB is associated with the EMT induced by CCL5 and CCL18 [145,146].…”
Section: Roles Of Chemokine System In Tumor Metastasismentioning
confidence: 99%
“…Interestingly, various chemokines have been implicated to contribute to EMT progression in cancer cells. EMT can be induced by CXCL8 and its receptors through overexpression of the transcription factor Brachyury [141], CCL2 with the enhancement of Snail expression [142], the CXCL6/CXCR1/2 axis via the PI3K/AKT and Wnt/β-catenin pathways [143], and the CXCL1/LCN2 paracrine axis with the activation of Src signalling [144]. In addition, NF-κB is associated with the EMT induced by CCL5 and CCL18 [145,146].…”
Section: Roles Of Chemokine System In Tumor Metastasismentioning
confidence: 99%
“…Recent studies have reported that CXCL1 is a key molecule leading to EMT and plays an important role in the development of various malignancies and metastasis. 22,23 Moreover, its high expression is associated with poor prognosis. 23 In this study, we showed for the first time that low-dose radiation can significantly upregulate the expression of CXCL1.…”
Section: Discussionmentioning
confidence: 99%
“…Lipocalin 2 (LCN2) is a secreted glycoprotein of lipocalin superfamily that is an important innate immunity component against bacterial pathogens and various cellular stress (19). Abnormal expression of LCN2 plays an extremely important role in the epithelial-to-mesenchymal transition process, angiogenesis, and cell migration and invasion in several cancers by involving multiple signaling pathways (20). A lot of research has indicated that LCN2 is correlated with high-grade malignancy, relapse proneness, metastasis and poor prognosis in epithelial-derived tumors (21).…”
Section: Discussionmentioning
confidence: 99%